Asociación entre polimorfismos del gen NAT2 y fisura labiopalatina no sindrómica en Argentina - Santos, María Rita (2015)
Background: NAT genes are considered candidate genes for the genetic predisposition to non-syndromic Cleft lip with or without cleft palate (NSCLP), since they codify for N-acetyltransferases, enzymes responsible for the biotransformation of arylamines, hydrazine drugs, and a great number of toxins and carcinogens present in diet, cigarette smoke, and environment. Aim: To determine the association between alleles determining slow acetylator phenotype and the risk of NSCLP. Material and methods: We analyzed *5 (481C>T), *6 (590G>A) and *7 (857G>A) alleles which determine the slow acetylator phenotype and *4 (wild type) allele by polymerase chain reaction/restriction fragment length polymorphism in 97 progenitor-case trios of NSCLP in Argentinian Obstetric Wards. We evaluated the transmission disequilibrium (TDT). Results: TDT showed a positive association between allele *5 and NSCLP (odds ratio=1.6; p=0.03). Conclusions: The presence of *5 allele is significantly higher in cases with congenital NSCLP.